Nature’s pillar / Muhammad Fawwaz Hadi Mohd Rafaie ... [et al.] - Mohd Rafaie, Muhammad Fawwaz Hadi; Mohd Razali, Ahmad Nizar Nazmi; Ujang, Muhammad Akmal Rizal; Mohamad Nor, Nadia Qistina (2024)
“Nature’s Pillar” is a place for all students, a refuge, and a community temple designed around sustainable living and active social involvement. Sustainably forested timber construction provides a living, earthbound hug that grows with each story. It drowns the room in sunshine and clean lines, providing both inclusivity and liveliness. It isn’t a matrix; it’s a chance to engage. Through its ambiguous boundaries, the design blurs the line between more outdoor spaces and provides a vision that allows students to walk beyond the confines of their home and into wider social engagement. Numerous locations have a place. One corner resonates with laughter as students decompress with games; another host’s cosy seating for relaxation or huddling; yet another facilitates conversations – creating a platform for students to come together, get to know each other, and establish a community. But the harmony is more than visual; it scientifically supports a balance, a yin and yang, between pursuits and well-being, to ensure every student finds both productivity and peace under one well-designed roof.